2022
DOI: 10.1021/acsaelm.2c00423
|View full text |Cite
|
Sign up to set email alerts
|

Organic Heterojunction Transistors

Abstract: Creating a tightly interacting semiconductor heterostructure and incorporating it into a transistor architecture is an important trend in materials research. This Spotlight on Applications aims to provide essential understanding of emerging high-performance organic heterojunction transistors with various materials, designs, and fabrication methods. This article also evaluates the current status of organic heterojunction transistor technology to clarify its future engineering challenges and opportunities. A spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Compared to 2D materials usually fabricated by a mechanical exfoliation method, organic materials, and their heterojunctions provide advantages regarding synthetic tunability, solution processability, and deposition scalability. [131][132][133][134] In 1995, the ambipolar characteristics were discovered in organic heterostructure transistors, explicitly utilizing a vertical p-type 6T/n-type C 60 molecular junction. [135] This breakthrough significantly advanced the development of organic light-emitting transistors and other organic heterojunction devices.…”
Section: Organic-based Heterojunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to 2D materials usually fabricated by a mechanical exfoliation method, organic materials, and their heterojunctions provide advantages regarding synthetic tunability, solution processability, and deposition scalability. [131][132][133][134] In 1995, the ambipolar characteristics were discovered in organic heterostructure transistors, explicitly utilizing a vertical p-type 6T/n-type C 60 molecular junction. [135] This breakthrough significantly advanced the development of organic light-emitting transistors and other organic heterojunction devices.…”
Section: Organic-based Heterojunctionsmentioning
confidence: 99%
“…Due to their inherent mechanical flexibility, lightweight nature, and low-cost fabrication, flexible organic electronics are promising building blocks for future IoT devices. [131] This also recently attracted much research interest in mechanical flexible ternary inverters based on organic semiconductor materials. [46,83,85] In 2021, Panigrahi et al reported the first flexible organic AAT and ternary inverter based on polyethylene naphthalate (PEN) substrate, as presented in Figure 22a,b.…”
Section: Organic Materials-based Ternary Invertersmentioning
confidence: 99%
“…A promising approach to MVL implementation is the use of p-n heterojunction-based antiambipolar transistors (AATs), which exploit the negative differential transconductance (NDT) characteristics of such heterojunctions. [9][10][11][12] AATs enable the fabrication of MVL circuits, including ternary and quaternary logic circuits, using only two transistors. [13][14][15][16][17][18][19][20][21][22] Moreover, the NDT characteristics of AATs enable the implementation of electrically reconfigurable logic gates, achieving multiple logic gate operations using a single "double-gated AAT" that are not obtainable in conventional p or n-type transistors.…”
Section: Doi: 101002/admt202301049mentioning
confidence: 99%
“…[14][15][16] The construction of a heterostructure channel layer using p-type and n-type semiconductor materials can realize the dual channel transmission of holes and electrons while also allowing for the controllable adjustment of bidirectional photoresponse under light illumination. [17] The photoresponse effect can be classified as positive or negative based on whether the channel photocurrent of the phototransistor increases or decreases in response to light. [18] At present, the study of photoresponse in organic materials is primarily focused on the positive photoresponse of the photoelectric effect.…”
Section: Introductionmentioning
confidence: 99%